2018
DOI: 10.2147/copd.s170887
|View full text |Cite
|
Sign up to set email alerts
|

Life-Space mobility and clinical outcomes in COPD

Abstract: BackgroundSocial isolation is a common experience in patients with COPD but is not captured by existing patient-reported outcomes, and its association with clinical outcomes is unknown.MethodsWe prospectively enrolled adults with stable COPD who completed the University of Alabama at Birmingham Life Space Assessment (LSA) (range: 0–120, restricted Life-Space mobility: ≤60 and a marker of social isolation in older adults); six-minute walk test (6MWT), and the University of California at San Diego Shortness of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
1
29
0
1
Order By: Relevance
“…Appendix Table 2 summarizes the characteristics of the 17 longitudinal/prospective studies that have examined LSM as a predictor over time of health outcomes such as cognitive decline, health care utilization (physician visits, hospitalizations, and hospital readmissions), admission to nursing homes, incidence of falls, quality of life, and mortality 18 , 21 , 66 78 For example, Crowe et al 68 examined the relationship between LSA and subsequent change in cognitive function over four years in participants from the UAB Study of Aging. The authors found that greater life-space at baseline predicted less decline over the 4-year period, after controlling for all covariates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Appendix Table 2 summarizes the characteristics of the 17 longitudinal/prospective studies that have examined LSM as a predictor over time of health outcomes such as cognitive decline, health care utilization (physician visits, hospitalizations, and hospital readmissions), admission to nursing homes, incidence of falls, quality of life, and mortality 18 , 21 , 66 78 For example, Crowe et al 68 examined the relationship between LSA and subsequent change in cognitive function over four years in participants from the UAB Study of Aging. The authors found that greater life-space at baseline predicted less decline over the 4-year period, after controlling for all covariates.…”
Section: Resultsmentioning
confidence: 99%
“…In examining clinical exacerbations in patients with COPD leading to emergency room visits or requiring hospitalization, Iyer et al 18 found that those with restricted LSM had a significantly reduced score on the 6-minute walk test, more severe dyspnea, worse quality of life, and greater depressive symptoms after one year of enrollment. Lo et al, 73 studying neighborhood disadvantage and LSM as predictors of incident falls, found that every 10-point decrease in LSA score increased the risk for one or more falls at six months after baseline assessment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spirometry is mandatory for establishing a diagnosis of chronic obstructive pulmonary disease (COPD) but is not sufficient for a general clinical assessment and evaluation of potential treatment effects. Functional performance assessed at walk or bicycle exercise tests together with measurements of symptoms and healthrelated Quality of Life (QoL) provide valuable additional information about present disease status, as well as prediction of future risk of exacerbations and disease prognosis [1][2][3][4][5][6][7]. The standard bicycle exercise protocol for cardiopulmonary exercise testing (CPET) measures the endurance time of cycling during a standard endurance test, at a constant rate of 75% of the maximum exercise workload (W MAX ) [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%